A Facile Synthesis of 8-Bromo-3-methyl-7-(b-D-ribofuranosyl)purine-2,6-dione with SnCl4 under Vorbruggen Glycosylation Conditions - Kumar Madana, Srujana Suneel; Sethuraman, Velusamy; Gupta, Nitin (Asian Journal of Chemistry, 2015)
In course of the synthetic studies of 8-bromo-3-methyl based nucleosides, we have developed a high regeo selective synthetic route to acquire N-7 isomer in the presence of different Lewis acids. The glycosylation reaction was performed with tin(IV) chloride as a Lewis acid instead of TMSOTf to avoid the emulsion formation, cross contamination of trifluoromethanesulfonic acid (TfOH) in the isolated product with similar yields (70 %). The concentration of sodium methoxide solution, reaction time and reaction temperature was studied for the successful deprotection of sugars. The consistent heavy metal (tin) lower limit in the range of 10-15 ppm obtained at various scales in isolated nucleosides, which can be pharmaceutically accepted as per ICH guidelines.